PHENOMENAL HOLISM AND QUALIA CATEGORIES (Revista Română de filosofie analitică, 2025)
Scientists have attempted to find consciousness and, more specifically, qualia in the physical world ever since philosophers such as Thomas Nagel (1974) or Frank Jackson (1986) have commented upon the elusive experiential properties of such mental states that are characterized by a specific “what’s it like”. One of the proposals to minimize the metaphysical and epistemological tension that arises once the existence of such phenomena is acknowledged originates in the influential paper “What is it like to be a bat?” (Nagel, 1974): the development of an objective phenomenology. Current research programmes follow this idea and aim to understand consciousness using mathematical-empirical models. However, these endeavors seem to be missing the point when studying consciousness because they do not provide any evidence about how qualia correspond to neural states. I argue against a proposal to account for the missing link between physical structures and qualia, namely the use of category theory (Tsuchiya et al., 2016). Instead, I conjecture that the endeavor is futile because it relies on the assumption that qualia can be described structurally from an epistemological point of view. I support my conjecture arguing that phenomenal holism has not been ruled out.